An introduction to Confucianism - Yao, Xinzhong (Cambridge University Press, 2013)
Taking into account the history and range of Confucian Studies, this book introduces Confucianism - initiated in China by Confucius (551 BC-479 BC) - primarily as a philosophical and religious tradition. It draws together the many strands of Confucianism in a style accessible to students, teachers, and general readers.